Analysis of Perfect Sentences and Imperfect Sentences in Detik.Com News Articles - Safitri, Rahmayani; Amri, Yusni Khairul (BIRCU, 2024)
Sentences are fundamental in language learning. Indeed, it is mainly through sentences that speakers can express their meaning completely and clearly. Linguistic units that we already know before reaching the sentence level are words (for example, I don't know) and phrases or groups of words (for example, I don't know). Words and phrases cannot express meaning completely and clearly unless they function in a subordinate sentence or as a response to a statement. Types of Sentences According to the Completeness of their Elements. Viewed in terms of the completeness of their elements, they are divided into two, namely perfect sentences (major) and incomplete sentences (minor).